COMPARISON OF CYSTATIN C LEVEL IN TEAR FLUID AND SERUM AS BIOMARKERS IN PRIMARY OCULAR TUMORS: Oral Presentation - Observational Study - Resident - Ayu Aliyah; Rodiah Rahmawaty Lubis (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Cystatin C is known to play a role in tumor development and is expected to be used as a biomarker in eye tumors. This study aims to compare Cystatin C levels in tear fluid and serum as biomarkers in primary ocular tumors. Methods : This study is an analytical observational study with a case-control design. A total of 25 subjects with eye tumors in the study group and 25 subjects without eye tumors in the control group were included. Sampling was conducted from April 2022-July 2022 at the Eye Polyclinic of the Reconstructive Ocuplasty and Oncology division. The Mann-Whitney test was used with a significance level of 5%. Results : There was a significant difference in the tear fluid Cystatin C level between subjects with eye tumors and without eye tumors (p<0.001), with the mean tear fluid Cystatin C in the eye tumor group of 1.43 mg/dL. There was no significant difference in serum Cystatin C levels between groups of subjects with malignant eye tumors and benign eye tumors. However, there was a significant difference in the level of tear fluid Cystatin C between the groups of subjects with malignant eye tumors and benign eye tumors (p=0.042). Conclusion : In the case group, there was a significant relationship between tear fluid cystatin C levels and eye tumors (p < 0.001).